2007
DOI: 10.1063/1.2777998
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen dissociation degree in the diffusion region of a helicon plasma source obtained by atomic lines to molecular band intensities ratio

Abstract: Estimates of the dissociation degree in the diffusion region of a nitrogen helicon plasma source based on optical emission spectroscopy and Langmuir probe measurements are presented. The estimation procedure relies on measurements of the ratios of the intensities of the atomic triplet 3pS04→3sP4 (742.36, 744.23, and 746.83nm) to the intensity of the 4-2 band of the first positive system (AΣu+3→BΠg3) at 750.39nm and the measured relative vibrational distribution of the BΠg3 state. The electron energy distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…The dissociation rate of nitrogen molecules can be defined as D ¼ ½N=2½N 2 , where ½N and ½N 2 are the number densities of N and N 2 in the plasma. Several studies have demonstrated both theoretically and experimentally that the intensity ratio of atomic and molecular nitrogen emission correlates well with D [8][9][10]. However, in our case the N lines are not spectrally resolved and they are superimposed onto the molecular bands, as shown in Fig.…”
Section: Optical Emission Spectroscopymentioning
confidence: 80%
“…The dissociation rate of nitrogen molecules can be defined as D ¼ ½N=2½N 2 , where ½N and ½N 2 are the number densities of N and N 2 in the plasma. Several studies have demonstrated both theoretically and experimentally that the intensity ratio of atomic and molecular nitrogen emission correlates well with D [8][9][10]. However, in our case the N lines are not spectrally resolved and they are superimposed onto the molecular bands, as shown in Fig.…”
Section: Optical Emission Spectroscopymentioning
confidence: 80%
“…I N/N 2 are the measured intensities of the spectral emissions from excited N and N 2 respectively, and n N/N 2 are their corresponding densities [2], [6], [7]. Our trilayer deposition system, discussed in detail elsewhere [1], [8], was equipped with an Ocean Optics USB4000 Spectrometer and a 1 inch diameter collimating lens to record optical emissions from a nitrogen ICP.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…To determine the relative amount of dissociated nitrogen in the plasma, we made the assumption that the observed plasma spectrum is mainly a superposition of the diatomic N 2 spectrum and discrete spectral lines associated with atomic N. For the spectrum of diatomic N 2 , we focus our attention to the well-studied B 3 Π g − A 3 Σ u first positive system, which is the most prominent diatomic band with high intensity spectra appearing from 478 to 2531 nm [10]. For the spectrum of atomic nitrogen, we focus on the 3p 4 S 0 → 3s 4 P nitrogen atomic triplet, as it lies within the range of optical emission captured by our spectrometer, overlapping spectra from the B 3 Π g − A 3 Σ u system, and is one of brightest emissions from atomic N in plasmas [7]. To extract the separate N and N 2 spectra, a similar approach to the one used by Endo [2] is implemented and described below.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…For the electron collisions (1)-(8) impact cross sections σ (E) are used ( [33][34][35]; for (7), (8) shifted according to threshold energies) which are convolved with a Maxwellian EEDF, whereas processes (1)-(3) are evaluated by detailed balancing.…”
Section: Electron Impact Processesmentioning
confidence: 99%